Qualitative Analysis of The Relationship of Mcgregor and Maslow's Theory of Motivation with Employee Productivity in Harfiah Laundry - Harries Madiistryanto; Aulia Kusuma Wardani; Anshori Anshori (PT. Publikasiku Academic Solution, 2023)
This research aims to analyze the qualitative relationship between McGregor and Maslow's motivation theories and employee productivity at Laundry Harfiah, a service company in the field of electronic equipment production. In background, research highlights the importance of motivation in increasing employee productivity and company success. McGregor's motivation theory (theories X and Y) and Maslow's hierarchy of needs theory are the focus for understanding and implementing in human resource management. The research was conducted using a qualitative approach and case study method, with research participants in the form of five Harfiah Laundry employees who had worked for at least one year. Data was collected through in-depth interviews, direct observation, and document analysis related to the application of motivation theory in companies. The research results show that Literal Laundry has successfully implemented McGregor and Maslow's motivation theories in human resource management. McGregor's theory is realized through policies that give employees the freedom to determine work schedules and participate in decision making. Meanwhile, Maslow's theory is applied through adequate salaries and benefits as well as training programs to meet the needs and self-actualization of employees. The positive relationship between the application of motivation theory and employee productivity is clearly visible, where motivated employees work better. Factors such as organizational culture, leadership, and employee involvement in decision making also influence the implementation of employee motivation and productivity. The conclusion of this research is that the application of McGregor and Maslow's motivation theory at Harfiah Laundry has a positive impact on employee productivity. Recommendations for companies include strengthening an organizational culture that supports employee motivation, increasing employee engagement, providing recognition for hard work, and continuing research for further understanding. Future research can use a quantitative approach and involve more companies and other variables to deepen understanding of the relationship between employee motivation and productivity.